Memberdayakan Jangkauan Global: Strategi Tripod untuk Internasionalisasi UKM di Sektor Produk Alam - Nandiroh, Umi; Sudarmiatin , Sudarmiatin (CV. AFDIFAL MAJU BERKAH, 2024)
This study analyzes the implementation of the tripod strategy—encompassing resource-based view (RBV), institution-based view (IBV), and industry-based view (IBD)—to support the internationalization process of SMEs, with a case study on Agronesian Indonesia, an SME operating in the natural agricultural products sector. A qualitative approach was employed, utilizing a case study design where data were collected through in-depth interviews, observations, and document analysis to gain a holistic understanding of how these three perspectives are applied. The findings indicate that integrating RBV, IBV, and IBD enables Agronesian to overcome resource constraints, leverage institutional support, and adapt products to international market demands, especially regarding sustainability. Theoretical implications of this study strengthen the literature on SME internationalization by highlighting the value of a combined approach, while practical implications provide a framework for other SMEs to design adaptive and structured internationalization strategies. The limitations of this research include a focus on a single case and reliance on qualitative methods, which restrict broader generalization. Future studies are recommended to involve a wider range of SMEs from various industries and to explore the influence of global shifts, such as trade policies and sustainability trends, on the effectiveness of the tripod strategy for SME internationalization.